Evaluating the Teaching of Physical Science Practical Work at a Selected Resource-Constrained Secondary School in Rundu Circuit, Kavango East Region - Tomas Shivolo; Cornelin Urungi Kamina; Gabriel Nembenge; Martha Mewiliko Nangutuwala; Fredrick Simataa Simasiku (Scientia Publica Media, 2024)
This study evaluated the teaching of Physical Science practical work at a resource-constrained secondary school in the Rundu Circuit, Kavango East region in Namibia. The research objectives were to assess the impact of practical work on learners’ academic performance in a resource-constrained community, identify the challenges faced by both teachers and learners in conducting practical activities, and propose strategies to address these challenges and improve the overall quality of science education. A qualitative research design was employed, with data collected through semi-structured interviews involving four Physical Science teachers. The interviews were analyzed using thematic analysis, with themes aligned to the research objectives. The findings revealed that the state of science practical work was poor due to a lack of sufficient laboratory equipment and resources. Other significant challenges identified included limited laboratory space, inadequate time allocation, overcrowded classrooms, a lack of motivation among learners, and insufficient background knowledge on practical work for learners. These challenges collectively impeded effective teaching and learning of science practical work. To overcome these issues, the study recommended providing adequate laboratory materials and constructing an additional laboratory to alleviate overcrowding. The study also further recommended the employment of laboratory technicians to assist teachers in organizing, planning and conducting practical activities more efficiently. Furthermore, the study suggested forming partnerships between schools to share laboratory facilities, as per Key Area 7 of the National Standard and Performance Indicators for Schools in Namibia, which emphasizes the importance of collaborative linkages within educational communities. By implementing these strategies, it was concluded that the quality of Physical Science practical work in resource-constrained schools could be significantly enhanced, leading to improved learner outcomes.